Análisis del Etnodesarrollo en el Departamento del Chocó: Una Mirada desde la Cosmovisión Afro. (2020)
From the analisys of the structure and organization of the black communities in Colombia and understanding from their worldview the importance which has the execution of ethnodevelopment plans for the exercise of their constitutional autonomy; this reflective work evidences the marked dissonance between the westernized development vision of the state and the worldview of the Afro communities, specifically those settled in the department of Chocó, a largely collective territory.